Regenerating urban historical fabric of Kerman with the emphasize on influential components on Satisfaction (Case study: Arg-Ganjalikhan, Mozafari, Ghaleh-Mahmood, Shora Park) - Mitra Ghorbi; Maryam Naghavi; Hamid Mohammadi (تحقیقات کاربردی علوم جغرافیایی)
Interactions and sometimes contradictions in economic and cultural priorities which happen due to social transformations, changes in paradigms and changes in economic – political systems led to changes in urban regeneration concept. The role of culture in urban regeneration had significant changes comparing to other factors; and the cultural focuses became the main approach in urban regeneration in recent decades. The quality of built environment and level of residents’ satisfaction plays an important role in regeneration policies of target areas as well. This study investigates the impact of environment quality variables (environmental, physical, economic and social) on level of residents’ satisfaction in cultural neighborhoods of Kerman, with the goal of improving the regeneration process.The method of this research is applied-developmental in terms of the aim, and descriptive and causal comparative in terms of the nature. This study uses questionnaire as a tool for collecting data. The study sample size is 513 and the data were analyzed by SPSS and AMOS softwares. The results demonstrate a significant direct relationship between economic and physical variables as well as social variables and consequently the same relationship between economic and the sense of satisfaction. The results also indicate a significant inverse relationship between environmental variables, which are effective on sense of satisfaction, and economic variables. The results of structural equation modeling (SEM) show that improvement in the condition of economic, physical and environmental variables, will improve condition of social variables and the sense of satisfaction in the studied neighborhoods. Furthermore, analysis showed that economic variables have more effect on social variables and eventually on the sense of satisfaction as compared to physical and environmental variables. Therefore, the negative effects of each four aforementioned factors could be decreased in the studied neighborhood through planning and application of culture-led regeneration policies. Accordingly the increase in the sense of satisfaction would improve the revitalization and sustainability in these neighborhoods.